Teaching inequity in vector-borne diseases management through a socioscientific issue framework - Nicole A. Scavo; Sarah Poor; Francisco C. Ferreira; Yuexun Tian; Julia Gonzalez; Jordan Salomon (One Health)
The distribution and management of vector-borne diseases (VBD) are affected by a social and cultural environment, including forms of systemic oppression such as racism and classism. University classes that cover these diseases usually focus on teaching biological concepts while skimming over other social, economic, and cultural factors that influence them. With no current lesson plan widely available to implement, we present a lesson plan intended to be delivered at the end of courses related to disease ecology to emphasize inequity issues that impact VBD management while also serving as a capstone for the biological content taught in the class. The lesson is based on the demographic and disease risk data from local contexts to provide effective place-based and socioscientific issues instruction. The lesson is designed as a role-playing simulation where groups of students are given separate disease outbreaks to combat with specific budgets. Therefore, each group has unequal resources to manage the disease depending on their specific local context. The simulation is followed by a discussion about equity in disease management. To make this activity broadly applicable, the lesson plan has been written in four languages (English, Portuguese, Spanish, and Mandarin) according to a diversity of corresponding locations (Texas-USA, Brazil, Spain, and China), which are included in the supplementary materials. Incorporating this lesson into curricula across multiple disciplines is an important step for developing future entomologists, parasitologists, epidemiologists, and other One Health professionals to address disparities in VBD control and help drive the field forward equitably.